Simple Life, Self-reliance, and Spirituality: Practice of Southern Thai Older Adults with Mental Health Problems in a Public Residential Home - Ngamwongwiwat, Benjawan; Kongsuwan, Vineekarn; Songwathana, Praneed (Pacific Rim International Journal of Nursing Research, 2025)
No study has explored the culture-related mental healthcare practices of older adults with mental health problems and mental illness living in residential homes in Thailand. Evidence regarding these practices is vital to deliver appropriate, quality care to these people. This focused ethnographic study aimed to explore the mental health care practices and the culture that influences them among older adults residing in a public residential home in southern Thailand. Data were collected through participant observations, document reviews, and individual semi-structured interviews with 10 key informants from November 2022 to May 2023. Data were analyzed using content analysis. Three central themes emerged from the data, each offering key insights into the mental health care practice: 1) maintaining a simple life for mental balance, 2) supporting self-reliance for independent living, and 3) cultivating meaning and mental resilience through spirituality and altruism. The participants emphasized the importance of nutritious diets, adequate sleep, time spent in nature, and engaging in leisure activities to maintain mental health. They also valued self-reliance by managing their symptoms through daily physical activities, receiving health care and social support from personnel, peers, families, and the community, and participating in therapeutic recreational activities. In particular, they engaged in Buddhist practices and altruistic behaviors to cultivate their life meaning and mental resilience. In sum, the interpretation of this ethnographic data underscores that mental health care among older southern Thai adults is best understood not as a set of clinical responses but as a culturally woven pattern of living grounded in simplicity, self-reliance, faith, and a lifelong pursuit of emotional equilibrium. The findings underscore the critical role of healthcare providers, particularly professional nurses who primarily provide all care aspects in the residential homes with no psychologists, in promoting simple, structured daily activities and emotional and psychological support in helping residents cope with their loneliness, stress, and anxiety. The study revealed the cultural and religious influences on mental health care practices, particularly the impact of Buddhism. The findings emphasized the importance of culturally sensitive mental health care to improve mental health and quality of life for older adults with mental illness.